Full-length genome sequencing and phylogeny of severe strain isolates of Tomato yellow leaf curl virus (TYLCV-IL) originating from Datura stramonium L. in Bojnurd region, Iran - Mohammad Reza Hossein Zadeh; Masoud Shams Bakhsh; Shahrokh Kazem Pour osalou (مجله بیوتکنولوژی کشاورزی, 2014)
Tomato yellow leaf curl virus (TYLCV) and  a complex of  ten virus species and their strains referred to as TYLCV-like viruses cause damage on tomato (Solanum  lycopersicum L.) crops in tropical, subtropical and temperate regions of the world.  In this study, full-length genome of three TYLCV-IL isolates originating from Datura stramonium L. in Bojnurd region, Iran were cloned, sequenced  and subsequently entered the phylogenetic analysis with nine TYLCV-IL isolates from Iran and eight selected begomoviruses of tomato from Iran and other part of  the world. The phylogenetic analysis suggested the geographical-dependent evolution of Iranian TYLCV-IL populations so that regardless of host species the monophyletic group of the northeastern and southern isolates was clustered separately into two subgroups. TYLCV-IL [IR: Sh40:07], GU076444 isolated in Shiraz region was not clustered with none of the Iranian TYLCV-IL isolates but rather was grouped with the type strain of TYLCV-IL from Israel in a separate group. Evolutionally, this isolate could be a “genetic bridge” between Mediterranean and Iranian TYLCV-IL isolates. This is the first report of Datura stramonium L. as the host species of TYLCV-IL in Iran and also the first-time occurrence of the viral stain in North Khorasan province, Bojnurd, Iran.